The impact of strategic thinking for administrative leadership on developing core capabilities: A field study on the Islamic International Arab Bank – Jordan - Alduhaisat, Hisham Khajael (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of this study is to explore the impact of strategic thinking for administrative leadership dimensions of systemic thinking, innovation, and vision in developing core capabilities at the Islamic International Arab Bank (IIAB), Jordan. The study followed the descriptive analytical approach. A questionnaire was developed for the data collection. The study population consists of 97 leaders, however, only 85 responses were obtained. The results showed that there was a discrepancy in the level of strategic thinking among administrative leaders, nonetheless, all the means in terms of the respondents’ perceptions were high, and there was a statistically significant impact of strategic thinking with its dimensions on the core capabilities of the IIAB. Based on the findings, strategic thinking for administrative leadership is recommended to be adopted as an approach for the development of core capabilities at IIAB, and increasing the interest on the strategic thinking for building core capabilities to achieve a high level of competence and better performance.